A theoretical and experimental study of adaptive wood composites - Smittakorn, Watanachai, author; Heyliger, Paul R., committee member; Thompson, Erik, committee member; Criswell, Marvin E., committee member; DuChateau, Paul, committee member (Colorado State University. Libraries, 2001)
A piezoelectric material is introduced to use with a wood element and produce an adaptive wood composite in a form of multilayered laminated plate. Steady-state and transient behaviors of the laminate are investigated under the coupled effects of mechanical, electrical, thermal and moisture fields. To analyze such a structure, a mathematical model in three dimensions, namely a discrete-layer model, is developed, treating the displacements, electric potential, temperature, and moisture concentration as primary unknowns. One-dimensional Lagrange linear interpolation functions are employed for the variation in the through-thickness direction. The variation in the two-dimensional in-plane domains is approximated by two approaches: analytical and finite element functions. Numerical examples verify the accuracy of the discrete-layer model by comparing with available exact solutions as well as demonstrate the behavior of adaptive wood composites subject to various types of excitations. The capability to actuate the composites and counter-balance unfavorable deformation by applying an electric field to the piezoelectric layer is then discussed. Also, representative experiments are conducted on adaptive wood composites in order to examine the degree of actuation induced by the piezoelectric phenomena and confirm the validity of the discrete-laver model.
Keywords: civil engineering; mechanical engineering